AB0975 Incidence of infections with biological therapies in paraguayan children with juvenile idiopathic arthritis: biobadaguay (biological therapies adverse events paraguayan-uruguayan register). (15th June 2017) - Morel, Z; Abreu, P De; Acosta, I; Avila, G; Cabrera, S; ,
Abstract : Background: Biological Therapies (BT) are important in the therapeutic arsenal of rheumatic diseases; however there is an increased risk of infections with their use. Objectives: To determine the frequency and type of infections in Paraguayan patients with Juvenile Idiopathic Arthritis (JIA), included in the BIOBADAGUAY Register. Methods: A prospective observational study of patients with JIA treated with BT, included in the BIOBADAGUAY Register. Patients at the onset of BT were included. The change and/or discontinuation of BT and the occurrence of adverse events (AEs) were recorded. Infectious events as affected organ, type, severity, outcome and need of temporary or permanent suspension of the biological agent were analyzed. Results: 59 patients with JIA and 69 BT were identified between May 2012 and December 2016. Female: 63% (37), Men: 37% (22). The mean age was 10 (3–18) years old. Mean disease progression of 2.8 (0.2–12) years from the diagnosis to BT beginning. JIA subtypes: poliarticular negative RF (27%), oligoarticular (27%: extended 22% and persistent 5%), enthesitis related arthritis (21%), systemic (12%), poliarticular positive RF (7%), psoriatic (3%), other (indeterminate) (3%). Biologic treatments: Adalimumab (ADM) 41 (59%), Etanercept (ETN) 19 (28%), Tolicizumab (TCZ) 9 (13%). There were 83 AEs of all treatments, 80 (96%) no serious and 3 (4%) severe with 1 death. Infections and infestations 54 (65%) of AEs were recorded. Of all TB infections: the 94% (51) were not serious and the 63% (34) required temporal discontinuation. Most infectious recovered without sequelae, except one death due to pneumonia (Table 1 ). Conclusions: 1) Infections and infestations (65%) were the AEs more frequently observed. 2) Of al Infections, respiratory tract iwere the most frequently observed. 3) Most of the infections were not serious and recovered without sequela. 4) The most frequently agent involved in infectious events was ADM (52% of all infections); even so it is most frequently administered agent. 5) Increased number of patients, greater diversity of treatment as well as a longer data to corroborate the observation period is required. Disclosure of Interest: None declared